(+)-Vitisin A inhibits osteoclast differentiation by preventing TRAF6 ubiquitination and TRAF6-TAK1 formation to suppress NFATc1 activation. - Wen-Fei Chiou (PLoS ONE, 2014)
We recently reported that oral administration of a (+)-vitisin A-enriched product prepared from Vitis thunbergii obviously ameliorated bone loss in ovariectomized mice and (+)-vitisin A was able to inhibit receptor activator of NF-κB ligand (RANKL)-induced osteoclast differentiation in RAW264.7 cells. Here we further clarified the mechanism(s) by which (+)-vitisin A targets osteoclastic differentiation and activity. Osteoclast-characteristic enzyme activity was determined using gel zymography or spectroflurometric-based assay. Expression of signal molecules was analyzed via Western blot or immunoprecipitation. Results showed that (+)-vitisin A suppressed RANKL-induced multinuclear cells (MNCs) formation and bone resorption which was accompanied with reduction in β3 integrin, osteoclast stimulatory transmembrane protein (OC-STAMP), matrix metalloproteinase-9 (MMP-9) and cathepsin K proteins expression. (+)-Vitisin A also down-regulated the proteolytic activities of MMP-9 and cathepsin K via targeting at the late stage function. (+)-Vitisin A prominently abrogated RANKL-triggered nuclear translocations of NF-κB, AP-1 (c-Fos/c-Jun dimer) and associated induction and nuclear accumulation of nuclear factor of activated T cells c1 (NFATc1). The upstream IκB degradation as well as ERK and JNK phosphorylation were also substantially repressed. Transfection with siRNA targeting tumor necrosis factor receptor associated factor 6 (TRAF6) clearly restrained RANKL-induced MNCs formation and NFATc1 induction. Interesting, RANKL triggered poly-ubiquitination of TRAF6 and associated TRAF6-TAK1 (transforming growth factor β-activated kinase 1) complex formation was prominently attenuated by (+)-vitisin A. Furthermore, the interaction between c-src tyrosine kinase (c-Src) and β3 was markedly induced by RANKL stimulation. (+)-Vitisin A significantly attenuated this interaction when concomitant treated with RANKL in RAW264.7 cells, but failed to affect c-Src/β3 complex formation when post-cultured with MNCs. Taken together, (+)-vitisin A suppressed bone resorption possibly via interruption of RANKL-induced TRAF6 ubiquitination and associated downstream signaling pathways. Furthermore, action through negative regulation of the proteolytic activity of MMP-9 and cathepsin K might also contribute to the anti-resorption effect of (+)-vitisin A.